2014
DOI: 10.1021/nl500337q
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing in Hybridized Arrays of Nanostrings

Abstract: We study high-Q nanostrings that are joined end-to-end to form coupled linear arrays. Whereas isolated individual resonators exhibit sinusoidal vibrational modes with an almost perfectly harmonic spectrum, the modes of the interacting strings are substantially hybridized. Even far-separated strings can show significantly correlated displacement. This remote coupling property is exploited to quantify the deposition of femtogram-scale masses with string-by-string positional discrimination based on measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…b. Arrays of mechanical resonators: Apart from optomechanical crystals, other realization of mechanical arrays based on nano-and micro-mechanical cantilevers, beams, and membranes, and that can be manipulated with either optical, electrical, or magnetic forces, could be used for our purpose [53][54][55][56][57][58]. In particular electromechanical arrays are very promising systems that are actively investigated in many experiments.…”
Section: A Alternative Implementationsmentioning
confidence: 99%
“…b. Arrays of mechanical resonators: Apart from optomechanical crystals, other realization of mechanical arrays based on nano-and micro-mechanical cantilevers, beams, and membranes, and that can be manipulated with either optical, electrical, or magnetic forces, could be used for our purpose [53][54][55][56][57][58]. In particular electromechanical arrays are very promising systems that are actively investigated in many experiments.…”
Section: A Alternative Implementationsmentioning
confidence: 99%
“…Phonon lasing, and hence an active mechanical resonator, has been experimentally realized in an electromechanical beam [71]. Elastically-coupled nano beams and cantilevers, by which the mechanical supermodes can be generated, have also been shown in various experiments [72][73][74][75], in which the two mechanical resonators can be independently driven [73]. Thus our proposal is within the reach of current experimental techniques of nano-microelectromechanical systems.…”
Section: On-chip Phonon Diodementioning
confidence: 63%
“…At the lowest RDX levels of 76 ± 3 and 42 ± 2 fg, only the main peak at 7.55 μm can still be seen. shown that these devices have a minimum detectable mass of 1.8 attograms (see the supporting information of Biswas et al 24 ).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In addition, the system we have demonstrated here can be extended to multiple adsorbed molecules, either directly through differentiation of the molecular IR signature 20 or through the use of arrays of nanostrings to detect molecules adsorbed to different strings in the array. 24 ■ ASSOCIATED CONTENT * S Supporting Information Experimental schematic, along with a description of the interferometric and photothermal techniques. This material is available free of charge via the Internet at http://pubs.acs.org.…”
Section: ■ Conclusionmentioning
confidence: 99%